Significant enhancement of fatty acid composition in seeds of the allohexaploid, Camelina sativa, using CRISPR/Cas9 gene editing - Jiang, Wen Zhi; Henry, Isabelle M.; Lynagh, Peter G.; Comai, Luca; Cahoon, Edgar B.; Weeks, Donald P. (Plant biotechnology journal, 2017)
Summary The CRISPR/Cas9 nuclease system is a powerful and flexible tool for genome editing, and novel applications of this system are being developed rapidly. Here, we used CRISPR/Cas9 to target the FAD2 gene in Arabidopsis thaliana and in the closely related emerging oil seed plant, Camelina sativa, with the goal of improving seed oil composition. We successfully obtained Camelina seeds in which oleic acid content was increased from 16% to over 50% of the fatty acid composition. These increases were associated with significant decreases in the less desirable polyunsaturated fatty acids, linoleic acid (i.e. a decrease from ~16% to <4%) and linolenic acid (a decrease from ~35% to <10%). These changes result in oils that are superior on multiple levels: they are healthier, more oxidatively stable and better suited for production of certain commercial chemicals, including biofuels. As expected, A. thaliana T2 and T3 generation seeds exhibiting these types of altered fatty acid profiles were homozygous for disrupted FAD2 alleles. In the allohexaploid, Camelina, guide RNAs were designed that simultaneously targeted all three homoeologous FAD2 genes. This strategy that significantly enhanced oil composition in T3 and T4 generation Camelina seeds was associated with a combination of germ‐line mutations and somatic cell mutations in FAD2 genes in each of the three Camelina subgenomes.